Organised crime and animals - van Uhm, Daan (Trends in organized crime, 2021)
This article provides an introduction to the special issue of Trends in Organized Crime on ‘Organised Crime and Animals’. The special issue contributes to the criminological literature on organised crime, new illicit markets and green criminology. The articles in this special issue offer a wide range of empirical evidence, criminological analysis and theoretical explorations of the various connections between organised crime and animals, including the illegal wildlife trade, gambling on animals, puppy trafficking, the killing of wolves and illegal, unreported fisheries and the regulatory and enforcement responses to these phenomena.